Stay or Leave: Director Identities and Voluntary Exit from the Board During Organizational Crisis - Withers, Michael C.; Corley, Kevin G.; Hillman, Amy J. (Organization Science, 2012)
Directors may play their most important role during organizational crisis; however, extant research suggests that they are often more willing to exit than remain on the board of a firm facing a crisis. We develop theory regarding directors' voluntary exit by integrating insights from identity theories with the organizational crises literature. Specifically, we model how directors' individual, relational, and collective identities work sometimes in concert and other times in opposition to each other to influence directors' voluntary decisions to remain on or exit from a board facing an organizational crisis.